Influence of cross-head speed on resin-dentin shear bond strength - Hara, A. T.; Pimenta, LAF; Rodrigues, A. (Elsevier B.V., 2001)
Objective: To evaluate the influence of different cross-head speeds on shear bond strength test on the dentin surface.Methods: One hundred and twenty extracted bovine incisors were embedded in polystyrene resin. The specimens were prepared by wet grinding with 320-, 400- and 600-grit Al2O3 paper exposing dentin. After the application of the adhesive system Single Bond (3M) to etched dentin, the composite resin Z-100 (3M) was applied and light cured. The specimens were randomly assigned to four groups (n = 30). The shear bond strength tests were performed with an EMIC DL 500 universal testing machine at four different cross-head speeds: 0.50 (A); 0.75 (B); 1.00 (C); and 5.00 mm/min (D).Results: the mean values of shear bond strength in MPa (SD) were: A, 11.78 (3.91); B, 11.82 (4.78); C, 16.32 (6.45); D, 15.46 (5.94). The data were analyzed with one-way ANOVA and Tukey's test (alpha = 0.05). The results indicated that A = B < C = D. The fracture pattern was evaluated by visual analysis in a stereomicroscope (25 x). The percentage of fractures that occurred at the adhesive interface were: A, 92.5%; B, 91.6%; C, 70.0%; D, 47.0%. The Student's t-test to percentages ( = 0.05) indicated that there were no significant differences among A, B and C; A and B differed from D, and there was no significant difference between C and D.Significance: Different cross-head speeds may influence the shear bond strength and the fracture pattern in dentin substrate. Shear bond strength using cross-head speeds of 0.50 and 0.75 mm/min should be preferred. (C) 2001 Academy of Dental Materials. published by Elsevier B.V. Ltd. All rights reserved.
Keywords: shear bond strength; cross-head speed; adhesion